2012
DOI: 10.1029/2011jg001930
|View full text |Cite
|
Sign up to set email alerts
|

Attributing carbon changes in conterminous U.S. forests to disturbance and non‐disturbance factors from 1901 to 2010

Abstract: [1] Recent climate variability (increasing temperature, droughts) and atmospheric composition changes (nitrogen deposition, rising CO 2 concentration) along with harvesting, wildfires, and insect infestations have had significant effects on U.S. forest carbon (C) uptake. In this study, we attribute C changes in the conterminous U.S. forests to disturbance and non-disturbance factors with the help of forest inventory data, a continental stand age map, and an updated Integrated Terrestrial Ecosystem Carbon Cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
99
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(109 citation statements)
references
References 110 publications
(207 reference statements)
9
99
1
Order By: Relevance
“…Disturbances periodically released large amounts of C to the atmosphere and further changed stand age structures. Our study showed that NEP in Heilongjiang forests was greatly influenced by disturbance factors, which is consistent with previous studies (Zhang et al 2012). Reducing the occurrence of disturbances, particularly fire, will maintain a high level of NEP in Heilongjiang.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Disturbances periodically released large amounts of C to the atmosphere and further changed stand age structures. Our study showed that NEP in Heilongjiang forests was greatly influenced by disturbance factors, which is consistent with previous studies (Zhang et al 2012). Reducing the occurrence of disturbances, particularly fire, will maintain a high level of NEP in Heilongjiang.…”
Section: Discussionsupporting
confidence: 80%
“…The parameters of the InTEC model were first calibrated in that study, and then the parameters were calibrated further for China . Recently, the InTEC model was used to estimate the C balance in forest ecosystems of the United States (Zhang et al 2012. Most of the parameters used in this study were obtained from previous studies, including the maximum carboxylation rate (Vcmax), specific leaf area (SLA), sensitivity of the N fixation rate to temperature (QNfix), sensitivity of electron transport to temperature (ajm), sensitivity of Rubisco activity to temperature (avm), and actual leaf nitrogen content (Nl).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…The InTEC model is process-based, closely calibrated to FIA and other observational data, and validated at the regional scale (Box 3) (Zhang et al 2012). For northern Wisconsin we used a simple downscaling approach by extracting results based on the geographic boundary of Ecoregion 212 (Fig.…”
Section: Effects Of Climate Air Pollution and Natural Disturbancementioning
confidence: 99%
“…We used the Integrated Terrestrial Ecosystem Carbon Cycle Model (InTEC) to quantify the historical effects of disturbance factors (harvesting, fire, insect infestation) and nondisturbance factors (CO 2 concentration, N deposition, climate variability) on productivity and carbon stocks of the continental United States, including northern Wisconsin (Chen et al 2000a(Chen et al , 2000bZhang et al 2012). The InTEC model is process-based, closely calibrated to FIA and other observational data, and validated at the regional scale (Box 3) (Zhang et al 2012).…”
Section: Effects Of Climate Air Pollution and Natural Disturbancementioning
confidence: 99%